Pengaruh Kualitas Pelayanan dan Harga terhadap Keputusan Pembelian Air Minum Isi Ulang pada Depot Rakha Kabupaten Muaro Jambi - Furnamasari, Fenti; Arsa, Arsa; Diwantara, Victor (ARZUSIN, 2026)
Refill drinking water purchasing decisions are influenced by various factors, particularly service quality and price, but studies that specifically position Depot Rakha in Muaro Jambi Regency as the research object with local consumer characteristics remain limited. This study aims to analyze the effect of service quality and price on purchasing decisions for refill drinking water at Depot Rakha in Muaro Jambi Regency. This study used a quantitative approach with a causal survey design. The research sample consisted of 96 respondents selected using convenience sampling. Data were collected through questionnaires, then analyzed using validity testing, reliability testing, classical assumption testing, multiple linear regression, t-tests, and F-tests. The results showed that service quality had a positive and significant effect on purchasing decisions, with a calculated t-value of 7.372 > table t-value of 1.985 and a significance value of 0.000 < 0.05. Price also had a positive and significant effect on purchasing decisions, with a calculated t-value of 6.398 > table t-value of 1.985 and a significance value of 0.000 < 0.05. Simultaneously, service quality and price had a significant effect on purchasing decisions, with a calculated F-value of 51.687 > table F-value of 3.09. The conclusion of this study affirms that improving service quality and setting competitive prices play an important role in encouraging consumers’ purchasing decisions for refill drinking water. The implications of this study provide practical input for the management of Depot Rakha in strengthening service strategies and pricing policies to sustainably increase consumer loyalty and purchasing decisions.